Investigation of vertical mixing in raceway pond systems using computational fluid dynamics - Shen, Chen, author; Dandy, David S., advisor; Reardon, Kenneth F., committee member; Bradley, Thomas, committee member; Prasad, Ashok, committee member (Colorado State University. Libraries, 2021)
Raceway ponds are widely used as cost-efficient and easily set up outdoor algal cultivation systems. Growth rates strongly depend on cumulative light exposure, which can be predicted using accurate computational fluid dynamics simulations of the ponds' dynamics. Of particular importance in computing the three-dimensional velocity field is the vertical component that is responsible for transporting cells between light and dark regions. Numerous previous studies utilized one of the turbulence models derived from the Reynolds-averaged Navier–Stokes equations to predict the turbulent behaviors in raceway ponds. Because vertical fluid motion is secondary and the primary flow is in the horizontal plane, using one of the Reynolds-averaged Navier–Stokes turbulence equations has the potential to decrease the fidelity of information about vertical motion. In Chapter 2, large eddy simulation (LES) and k-ɛ models are used to simulate fluid dynamics in a mesoscale (615 L) raceway pond system and compared with laboratory data. It is found that swirling motions present in the liquid phase play an essential role in the vertical mixing performance. LES is shown to have the capability to provide more realistic and highly time dependent hydrodynamic predictions when compared with experimental data, while the k-ε model under-predicts the magnitude of the swirling behavior and over-predicts the volume of dead zones in the pond. The instantaneous spatial distribution of high vertical velocity regions and dead zones, as well as their time-accumulated volume fraction, are investigated. LES results suggest that swirling motion exists in the low-velocity regions predicted by the k-ɛ model to be dead zones where the high-velocity flow takes place over more than 50% of the flow time, and the recirculating motion may be responsible for stratification and unwanted chemical accumulation. LES results indicate that strong vortex regions exist near the paddle wheel, and the first 180°bend, and the geometry of the divider will contribute to the generation of vortices, enhance the vertical motion, and increase the light/dark effect. In Chapter 2, it will be demonstrated that the swirling motion appears to play a critical role in enhancing the vertical mixing and enhancing the light/dark effect. In Chapter 3, a dimensional analysis is performed to predict the persistence of the swirling motion generated at the hairpin bend by modeling 7 raceway pond geometries with shape ratios—defined as the ratio of the width of a straight section to the liquid depth—ranging from 0.5 to 7.05, and Dean numbers ranging from 16,140 to 242,120. The fluid dynamics were simulated using a transient multiphase solver with a large eddy simulation turbulence model in the open-source code open Foam framework. The results demonstrate that the number of instances of swirling motion strongly depends on the shape ratio of the ponds. When the shape ratio is close to 1, a single instance of swirling motion is most likely to be found downstream of the first 180° bend, while multiple occurrences of swirling motion are observed when the shape ratio is larger than 1. It was also found that the strength of the swirling motion has a linear dependence on the average velocity magnitude downstream of the first 180° bend after the paddle wheel. The strength and persistence of the swirling motion are fit with a rational function that can be used to predict the mixing performance of a raceway pond without the need for complicated and expensive simulations. In Chapter 4, transient particle tracking is performed to predict microalgae cells' vertical motion for more than 800 s, which is subsequently converted to the cells' light intensity history. The data of light intensity history, along with the velocity field, are compared to validate the hypothesis that the cells' trajectories and L/D transition are significantly dominated by vertical mixing in raceway ponds, mostly, the swirling motions generated by the secondary flow in the hairpin bends. It is found that the region where cells have a high probability to experience light/dark transitions coincides with the spatial prediction of swirling motion, suggesting that the swirling motion significantly contributes to reducing the light/dark frequency exposure by microalgae. In Chapter 5, a novel use of vortex generators in a raceway pond is presented that passively generate swirling motion in the regions where the strength of vertical motion is predicted to otherwise be low. The flow field is quantitatively simulated using computational fluid dynamics using the large eddy simulation turbulence model. Persistence lengths of the swirling motion generated by the vortex generators indicate that significant vertical mixing can be achieved by placing vortex generators in the straight section opposite the paddle wheel, downstream of the first hairpin bend. Relatively simple vortex generators are capable of creating stronger swirling motions that persist for a longer distance than those caused by the paddle wheel. For optimal performance, vortex generators are positioned side by side but in opposite directions, and their diameters should be equal to or slightly less than the liquid depth. The optimal length of a 0.18 m diameter vortex generator in a 0.2 m deep pond was determined to be 0.3 m. Furthermore, it has been demonstrated that a longer persistence length is achieved by inducing a swirling motion with its rotational axis parallel to the primary flow direction.
Keywords: microalgae; swirling motion; computational fluid dynamics; vertical mixing; raceway pond